Toleransi Antar Umat Beragama (Studi Kasus Keluarga Islam dan Keluarga Non Islam di 10 Ulu Palembang) - Yuniar Handayani; Ruskam Suaidi (El-Ghiroh : Jurnal Studi Keislaman, 2020)
This study aims to determine how the form of tolerance between religious communities in Rt 34 Kelurahan 10 Ulu, Jakabaring Sub-district in Palembang and to find out how the relationship between Islamic families and non-Islamic families in Rt 34 Kelurahan 10 Ulu, Jakabaring Sub-district in Palembang. The research approach uses a qualitative approach. The social situation in the community in the 10 Ulu Palembang neighborhood RT 34 that is Muslim and non-Muslim. The subjects of the study were the people in the 10 Ulu Palembang, RT 34 village who were Muslim and non-Muslim. Data collection techniques are observation, in-depth interviews, FGD, and documentation. Data analysis techniques use data presentation, data reduction, and data conclusions. The result of the research is that religious tolerance in RT 34 has occurred between Muslims and Confucianists. This can be seen from the location of the al Ghazali mosque with the kwan in goddess temples which are close together. And tolerance in the area of ​​9/10 ulu can also be seen from the harmonious life of the residents there. Even though they have different religions, they still help and help each other, if there are religious ceremonies carried out by Muslims, Congolese and Buddhists.